Few layered MoS2 lithography with an AFM tip: description of the technique and nanospectroscopy investigations. Issue 26 (17th June 2015) - Donarelli, M.; Perrozzi, F.; Bisti, F.; Paparella, F.; Feyer, V.; Ponzoni, A.; Gonchigsuren, M.; Ottaviano, L.
Abstract : A novel technique to lithograph the MoS2 surface is described here. Abstract : A novel technique to lithograph the MoS2 surface is described here. Mechanically exfoliated MoS2 flakes have been patterned with an atomic force microscope tip. After the patterning process, the lithographed areas have been removed by selective chemical etching. The electronic properties of the MoS2 flakes have been analyzed with spatially resolved photoelectron spectroscopy, with tunable incident photon energy, provided by a synchrotron light source. Tens of meV core level shifts can be recorded in relation to the flakes edges, coming from both the exfoliation and from the lithography.